Is Family-Centered Care Really Family-Centered in the Newborn Nursery?. Issue 3 (May 2016) - Beal, Judy A.
Abstract : Patient- and family-centered care is much talked about but not always reality in the care of mothers and babies during the inpatient stay for childbirth. It should be.